Localized pseudo-neoplastic idiopathic biliary strictures - Praderi, Raúl; Colet, Andrés; Parodi, Hernán; Kvasina, Tomislav; Pizzarossa, Carlos (Cirugía del Uruguay, 1986)
Presenting two cases of localized non neoplasic stenosis of the principal biliary duct in young women. They are topographied at the converging point of the hepatic duct and the distal choledoco. Wlth the neoplasm cholangiographic diagnosis, both were resected by exeresis of biliary tract in one of them and cephalic duodenopancreatectomy in the other.